A Narrative Review on Hormonal and Reversible Contraception: Advances, Options, and Implications for Reproductive Health - Krushan Shah; Bhagyesh Sapkale; Rajesh Godavarthi; Kamlesh Chaudhari (Journal of Clinical and Diagnostic Research, 2025)
This narrative-based systematic review aims to examine contraception, focusing on new developments and alternative techniques. Pregnant teenagers often face challenges regarding their social standing in society. To minimise teen pregnancy, the availability of services in terms of the supply of hormonal contraceptives and Long Acting Reversible Contraception (LARC) must be improved. There are many situations that require the use of Emergency Contraception (EC) to provide preventive measures after risky encounters. As there are currently no other male contraceptive options on the market, a male hormonal contraceptive is necessary. The market is primarily driven by contraceptive biomaterials, most of which are elastomers such as ethylene vinyl acetate and polydimethylsiloxane. Keywords from the Web of Science and PubMed databases included barrier techniques, LARC, contraception, and others. To maintain reliability and academic rigor, the inclusion criteria focused solely on English language research, reviews, and articles published in the last 10 years. Exploring new hormone combinations with better metabolic properties is an important aspect of the advanced conception of contraceptives. Lower androgenicity forms of natural chemicals and progestins are employed in LARC techniques to reduce thrombogenesis. Potential alternatives include transdermal systems and other vaginal rings. The sequelae, particularly the interactions between hormonal contraceptives and antiepileptic drugs, should also be discussed. Some types of contraception include tubal ligation through hysteroscopy, the impact of antiepileptic drugs on the effectiveness of hormonal contraceptives, and improved barrier methods of contraception. In certain medical contexts, Point of Care Contraceptives (POCCs) play important roles. This paper provides a comprehensive overview of contraceptives, their forms, and key considerations. The evaluation of LARC products for patient satisfaction, superior efficacy, and the promotion of condom use for the control of Sexually Transmitted Diseases (STDs) is also illustrated. According to this framework, reversible contraceptives provide people with greater control over family planning; Intrauterine Devices (IUDs) and subdermal implants are among the most effective contraceptive methods. The use of LARC techniques is discussed in this abstract, which underlines their importance and recognises that they are considered the most effective method of contraception when used regularly.